2021
DOI: 10.1080/10717544.2021.1971797
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunotherapy of chlorogenic acid liposomes modified with sialic acid and PD-1 blockers effectively enhances the anti-tumor immune response and therapeutic effects

Abstract: Melanoma is one of the most common malignant tumors. The anti-PD-1 antibody is used for the treatment of metastatic melanoma. Treatment success is only 35–40% and a range of immune-related adverse reactions can occur. Combination of anti-PD1 antibody therapy with other oncology therapies has been attempted. Herein, we assessed whether chlorogenic acid liposomes modified with sialic acid (CA-SAL) combined with anti-PD1 antibody treatment was efficacious as immunotherapy for melanoma. CA-SAL liposomes were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In our previous research, we have already proved the positive effect of chlorogenic and caffeic acid and a static magnetic field on melanoma cells in the aspect of oxidative stress, cell redox homeostasis and apoptosis [ 28 , 33 ]. In turn, Li et al [ 37 ] demonstrated the effectiveness of treatment consisting of a combination of sialic acid modified chlorogenic acid liposome therapy (CA-SAL) in combination with anti-PD1 (anti-programmed death protein 1) antibody treatment. Moreover, the research by Choi et al [ 38 ] also showed the positive effect of Phyllostachys nigra active compounds on melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, we have already proved the positive effect of chlorogenic and caffeic acid and a static magnetic field on melanoma cells in the aspect of oxidative stress, cell redox homeostasis and apoptosis [ 28 , 33 ]. In turn, Li et al [ 37 ] demonstrated the effectiveness of treatment consisting of a combination of sialic acid modified chlorogenic acid liposome therapy (CA-SAL) in combination with anti-PD1 (anti-programmed death protein 1) antibody treatment. Moreover, the research by Choi et al [ 38 ] also showed the positive effect of Phyllostachys nigra active compounds on melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…CGA prevents B16F10 melanoma cell proliferation by facilitating the tumor-associated macrophage (TAM) polarization from M2 to M1. CGA with an anti-PD1 antibody can decrease the CD4 + Foxp3 + T cell ratio and increase the CD8 + T cell ratio, leading to an enhancement of immunotherapeutic activity in vivo [289].…”
Section: Melanomamentioning
confidence: 99%
“…Molecular docking simulation and in vitro kinetic assay [312][313][314][315] Inhibition of α-MSH [312][313][314]; inhibition of tyrosinase [315] CGA [282]; leukemia cell lines U937, and HL60 [284,285]; lung cancer cell line A549 [287]; melanoma C32 and B16F10 [288,289]; glioma cells U87 [290]; osteosarcoma cell lines U2OS, MG-63, and Saos-2 [294,295]; pancreatic carcinoma PANC-1 [297,298]; prostate cancer cell DU145 [300]; and RCC A498 cells [301]; tumor-bearing SCID mouse models [282,287] Increase in p53, Bax, and the ratio of Bax/Bcl-2 [276,277]; blockages of (1) p-STAT-5 and p-CrkL [283,287], (2) the NF-kb pathway [276], (3) the STAT3/Snail pathway [294,295], (4) the PI3K/Akt/mTOR pathway [301], and EMT [276] CGA Cancer management in patients (Section 7.12)…”
Section: Pathogen Infectionsmentioning
confidence: 99%
“…Albeit various chlorogenic acid isomers exhibit salient advantages over their native counterpart, they occasionally betray certain toxicological concerns and adverse manifestations. Consequently, a panoply of chlorogenic acid encapsulation and delivery stratagems have been envisaged, encompassing liposomes, micelles, and nanoparticles, among others ( Li et al, 2021 ; Li et al, 2022 ).…”
Section: Chlorogenic Acid-loaded Delivery Systemsmentioning
confidence: 99%